2011
DOI: 10.1002/qua.23112
|View full text |Cite
|
Sign up to set email alerts
|

CASPT2 study on low‐lying states of HMgO and HOMg

Abstract: The HMgO and magnesium monohydroxide (HOMg) have been reinvestigated using the complete active space self-consistent field (CASSCF) and multiconfiguration second-order perturbation theory (CASPT2) methods with the contracted atomic natural orbital (ANO) basis sets. The geometries of all stationary points along the potential energy surfaces (PESs) were optimized at the CASSCF/ANO levels. The ground and the first excited states of HMgO are predicted to be X

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The high-level ab initio theoretical calculations indicated that the ground states of HMgO, 7 HOMg 7 and HAlN 6 are linear, which obey the Walsh rules. The high-level ab initio theoretical calculations indicated that the ground states of HMgO, 7 HOMg 7 and HAlN 6 are linear, which obey the Walsh rules.…”
Section: Introductionmentioning
confidence: 98%
“…The high-level ab initio theoretical calculations indicated that the ground states of HMgO, 7 HOMg 7 and HAlN 6 are linear, which obey the Walsh rules. The high-level ab initio theoretical calculations indicated that the ground states of HMgO, 7 HOMg 7 and HAlN 6 are linear, which obey the Walsh rules.…”
Section: Introductionmentioning
confidence: 98%